The Influence of Digital Service Quality, Platform Trust, and User Experience on Purchase Decisions on Shopee - Andi Muh Fachry; Afidah Nur Aslamah; Osly Usman; Ryna Parlyna (Asosiasi Transformasi Digital Dan Bisnis Indonesia, 2025)
Indonesia's e-commerce landscape has witnessed exponential expansion, with Shopee commanding 51 percent of market traffic, suggesting that particular digital platform elements substantially affect consumer purchasing behavior. This research aims to examine the impact of digital service quality, platform trust, and user experience on purchase decisions at Shopee, both individually and concurrently. Utilizing a quantitative methodology with explanatory research framework, this research employed Structural Equation Modeling-Partial Least Squares (SEM-PLS) to examine data from 64 active Shopee users in Indonesia who fulfilled inclusion criteria of being minimally 18 years old and having completed at least three transactions within six months. Measurement instruments exhibited excellent validity with Average Variance Extracted scores surpassing 0.50 and high reliability with Composite Reliability spanning from 0.887 to 0.912. Findings disclosed that user experience exerted the strongest impact with path coefficient of 0.349, succeeded by digital service quality (0.312) and platform trust (0.286), all statistically significant at p<0.05. Concurrent assessment validated that the three constructs collectively accounted for 74.3 percent of purchase decision variability with R² of 0.743, demonstrating substantial predictive capability. The research concludes that synergistic interaction among system efficiency, platform integrity confidence, and user experience quality generates cumulative effects stimulating digital consumption behavior. E-commerce platforms should optimize these three elements holistically to enhance purchase conversion rates and sustain competitive advantage in Indonesia's dynamic digital marketplace.